Implications of the 2021 CKD-EPI cystatin C/creatinine eGFR equation for eligibility for therapy in HFrEF: insights from PARADIGM-HF. (3rd October 2022) - Tolomeo, P; Kondo, T; Butt, J H; Desai, A S; Lefkowitz, M P; Rouleau, J L; Solomon, S D; Swedberg, K; Zile, M R; Campo, G; Jhund, P S; Packer, M; et al.
Abstract: Background: Estimated glomerular filtration rate (eGFR) is a key determinant of eligibility for many life-saving therapies in HFrEF. Recently, the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) provided new equations based on creatinine (CKD-EPIcr), cystatin C (CKD-EPIcys) or both (CKD-EPIcyscr) that do not include race. These new equations may reclassify individuals, irrespective of race, from one eGFR category to another, with implications for eligibility for HFrEF treatments. Purpose: To assess the difference between eGFR estimation using the 2021 CKD-EPIcyscr equation and the 2009 CKD-EPIcr and Modification of Diet in Renal Disease Study (MDRD)-4 equations which are still standard in many European laboratories. Methods: We included patients from PARADIGM-HF with cystatin C and creatinine values available at the time of randomization. For each patient, baseline eGFRs were calculated using the 3 equations described. Our focus was on patients with chronic kidney disease (CKD) stages III–V. Results: Overall, 1910 patients were eligible. Mean age was 67.3 (10.1) year and 385 (18.7%) were female. Using 2009 CKD-EPIcr, 779 patients were in CKD stages 3–5, of which 233 (30%) were reclassified to a better CKD stage (higher eGFR) with the 2021 CKD-EPIcyscr equation (Table 1). Similar reclassification was seen when comparing MDRD-4 with the 2021 CKD-EPIcyscr equation: 277 (33%) of 831 patients in CKD stages 3–5 were reclassified to a better CKD stage (Figure 1). Conclusions: The 2021 CKD-EPIcyscr equation favourably reclassified CKD stage in a large percentage of patients with HFrEF and a low eGFR, potentially increasing the proportion of these patients considered eligible for guideline-recommended therapies. Funding Acknowledgement: Type of funding sources: None.